Oral mucosal lesions in Polish patients with acute myeloid leukemia after allogeneic hematopoietic cell transplantation - Aleksandra Wysocka-Słowik; Zuzanna Ślebioda; Barbara Dorocka-Bobkowska; Marzena Liliana Wyganowska (Scientific Reports)
Abstract The number of allogeneic hematopoietic cell transplantation constantly increases. Therefore, there is an urgent need to carefully analyze the general and oral health state of people with acute myeloid leukemia who underwent this procedure. This study aimed to investigate the type and frequency of oral mucosal lesions in patients with acute myeloid leukemia after allogeneic hematopoietic cell transplantation, depending on the intensity of the conditioning regimen. Eighty patients diagnosed with acute myeloid leukemia were assigned to two groups based on the conditioning used before transplantation. The dental team investigated the oral mucosa in all patients thrice during the treatment. The most common oral pathological lesion in the study group was mucositis, which developed in a significantly higher percentage of patients who underwent myeloablation therapy compared to reduced intensity conditioning (p = 0.0335). Other frequently found eruptions included massive coating on the dorsal tongue surface, petechiae, and exfoliating cheilitis. The type of conditioning did not significantly influence their frequency. A significant increase in post-transplant lesions was observed on the lips, sublingual area, and floor of the mouth. There were no statistically significant differences in the site of lesions depending on the type of conditioning. Oral mucosal pathological changes in the study group were frequent. The type of conditioning influenced the frequency of mucositis but did not affect the frequency and the location of other types of oral mucosal lesions. Providing the patients qualified for chemotherapy with professional dental support is important.